BOUVERT'S SYNDROME: A CASE REPORT - Hadzi - Manchev, Dragan; Ognjenovik, Ljubomir; Osmani, Bujar; Shumkovski, Aleksandar; Gjoshev, Stojan; Dzambaz, Darko; Hadzi-Manchev, Todor; Bileski, Dejan (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Introduction :  Bouveret’s syndrome is a gastric outlet obstruction caused by an impacted gallstone that enters the stomach through a cholecystogastric or cholecystoduodenal fistula.   Case Presentation : A 66-year-old female patient presented one month prior to admission at our clinic with symptoms of nausea, vomiting, jaundice, and pain under the right costal arch. An abdominal ultrasound revealed aerobilia without dilation of intrahepatic bile ducts. An ERCP showed a significant amount of bile in the stomach and a rounded foreign object—a gallstone—inside the stomach. An unsuccessful attempt was made to extract the stone. While under general anesthesia, a gastroscopy revealed a large gallstone in the gastric antrum and a cholecystogastric fistula with significant bile leakage. Surgical treatment included cholecystectomy with partial gastric wall excision, stone extraction, and gastrostomy closure.  One-stage surgical treatment involves enterolithotomy, cholecystectomy, and fistula repair. Two-stage treatment is reserved for patients with unstable vital signs and typically involves endoscopic enterolithotomy followed by delayed cholecystectomy and fistula repair.   Keywords : Bouveret syndrome, biliary calculus, cholecystogastric fistula, cholelithiasis, gallbladder.